William H. Conkling papers - Conkling, William H., 1858-1939.
Correspondence with Charles A. Lindbergh, speeches, writings, publications, photographs, and memorabilia relating to Lindbergh's cross-country airmail route which included service to Springfield, Ill., and his flight from New York to Paris. Includes a philatelic cover which Lindbergh carried aboard the Spirit of St. Louis on his trans-Atlantic flight and mailed to Conkling from Paris.
Municipal government official, civic leader, and postmaster from Springfield, Ill.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Lindbergh, Charles A. -- 1902-1974.; Spirit of St. Louis (Airplane); Air mail service; Covers (Philately); Postal service -- Illinois -- Springfield; Transatlantic flights; Civic leaders; Postmasters; Public officials